2006
DOI: 10.1002/cbf.1383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indole‐3‐acetic acid administration by gavage and by subcutaneous injection on rat leukocytes

Abstract: This study was done to investigate the effect of indole-3-acetic acid (IAA) administered subcutaneously and by gavage on neutrophil function and cytotoxicity in neutrophils and lymphocytes. A gavage administration resulted in an increase in phagocytic capacity in neutrophils in a dose depended manner for 1 mg, 2 mg, 18 mg, and 40 mg of IAA per kg of body mass, respectively, compared with the control. Similarly, subcutaneous administration of IAA at 2, 18, and 40 mg per kg of body mass promoted a significant ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
(40 reference statements)
1
7
0
2
Order By: Relevance
“…Recent studies shown that orally or subcutaneous IAA has no toxic action on rats leukocytes measured by analyzing the DNA integrity, membrane integrity, and enzyme activities. [12][13][14] However, the genotoxic carcinogen DEN induced extensive DNA damage 42 in accordance with the present study. Moreover, IAA was partially efficient in providing protection to DENinduction of DNA fragmentation; similarly, guarana has a protective effect against DEN-induced DNA damage in mouse liver.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent studies shown that orally or subcutaneous IAA has no toxic action on rats leukocytes measured by analyzing the DNA integrity, membrane integrity, and enzyme activities. [12][13][14] However, the genotoxic carcinogen DEN induced extensive DNA damage 42 in accordance with the present study. Moreover, IAA was partially efficient in providing protection to DENinduction of DNA fragmentation; similarly, guarana has a protective effect against DEN-induced DNA damage in mouse liver.…”
Section: Discussionsupporting
confidence: 92%
“…11 Recent studies have shown that oral or subcutaneous administration of IAA can promote a possible beneficial effect by increasing the phagocytic capacity of rat neutrophils. 12,13 This auxin administration does not have a deleterious effect on leukocytes and liver of rats 14 and the IAA does not have an effect on metabolic enzyme activities in mice kidneys. 15 The prevention of several diseases by many natural substances has been associated with the antioxidant action of these compounds upon depletion of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 93%
“…It can be oxidized by the enzyme horseradish peroxidase (HRP) producing cytotoxic compounds, mainly hydroxyl and reactive oxygen species (ROS), able to destroy human cancer cells by membrane and DNA damage . IAA is not easily oxidized by mammalian peroxidases and, therefore, it is well tolerated in humans and even presents positive effects such as an increase in the phagocytic capacity of neutrophils or antioxidant activity . Therefore, the necessity to avoid the premature release of the housed pro‐drug from the silica matrix is not as important as in the case of transporting conventional cytotoxic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It can explained because no behavioural changes were observed in animals treated with IAA with such irritability, weakness in the legs and myotonia, lassitude and immobility as observed by other authors by using higher doses of IAA. However, the doses of IAA used here are the same, which did not alter the integrity of neutrophils . Thus, the presence of IAA in the brain generated during the metabolism of tryptophan can contribute to leave at development of neurodegenerative diseases, and the monitoring of brain electric activity by EEG proved effective in evaluating this situation.…”
Section: Discussionmentioning
confidence: 91%
“…The presence of peroxidase IAA acts as a prooxidant substance and generates oxidative stress by an increased formation of reactive oxygen species (ROS) . However, studies have showed that oral or subcutaneous administration of IAA increased the phagocytic capacity of neutrophil and do not have deleterious effect of rat livers and mice kidneys . Moreover, IAA showed potent antioxidant effects and warned the mice livers against hepatocarcinoma induced by N‐nitrosodietilamina (DEN) .…”
Section: Introductionmentioning
confidence: 99%